Pemberdayaan UMKM Tahu Goreng Kremes Di Br. Anyar-Kediri, Tabanan - Mahendra, Tubagus; Ayu, Putu Desiana Wulaning; Purnama, I Gusti Agung Vony; Huizen, Roy Rudolf; Pradipta, Gede Angga; Liandana, Made (Sevanam: Jurnal Pengabdian Masyarakat, 2024)
Tofu is rich in protein, making it good for daily consumption. Its delicious taste and affordable price make tofu a favorite food for people from various backgrounds. The increase in soybean prices does not prevent tofu entrepreneurs from continuing their production. Similarly, the reason why community service partners have started their own small independent businesses that produce various flavored fried tofu is that the raw material in the form of tofu is easily obtained and the price is still affordable, even though it has increased. The partners in this community service started their business in 2020. The crispy fried tofu produced by the partners is named Tahu OPPA, employing four employees, and the partners need a medium that can introduce their products and businesses to more people. This can help increase consumer awareness about the existence of the partner's business. Since starting the crispy fried tofu business, the partners have faced obstacles in terms of knowledge and skills to create and manage a website, as well as obstacles in digital marketing strategies to attract customers to make purchases of their products. The activity began with an analysis of the partner's situation, followed by providing assistance to the partners in creating a business profile website. The second activity continued with providing an understanding of digital marketing strategies utilizing social media to encourage consumers to make purchases